Treatment of cataplexy. (March 2013) - De la Herrán-Arita, Alberto K; Equihua-Benítez, Ana C; Drucker-Colín, René
<x xml:space="preserve">Abstract</x> Introduction: The term cataplexy originates from the Greek κατά (kata, 'down'), and πληξις (plexis, 'stroke'). Cataplexy, a sudden loss of muscle tone in response to strong emotions is the most specific symptom of narcolepsy. It is thought to be due to disturbed rapid eye movement (REM) sleep regulation and portrayed as REM sleep atonia occurring at the wrong time. However, there are several arguments against including cataplexy in the 'state boundary control' hypothesis. Cataplexy is most likely secondary to the disruption of different neurological pathways and eliciting the mechanisms by which cataplexy unfolds still remains an undergoing challenge. Areas covered: In this review, the authors appraise the neurobiology of cataplexy and emphasize the prospective approaches for the treatment of this ailment. The authors describe current pharmacological approaches that address this symptom, such as serotonergic and noradrenergic agents and γ-hydroxybutyrate. In addition, drugs that are still in the preclinical phase, such as triple reuptake inhibitors, thyrotropin-releasing hormone, histamine agonists and hypocretin are also reviewed. Finally, the authors conduct a comprehensive analysis of the various promising future treatments for cataplexy. Expert opinion: Cataplexy remains a fascinating symptom, showing complex interactions between systems involving emotions and those involved in motor control. Incorporating and integrating this knowledge will be imperative to further understand and treat this phenomenon.